Seasonal, inter-annual and solar cycle variability of the quasi two day wave in the low-latitude mesosphere and lower thermosphere. (January 2017) - Rao, N. Venkateswara; Ratnam, M. Venkat; Vedavathi, C.; Tsuda, T.; Murthy, B.V. Krishna; Sathishkumar, S.; Gurubaran, S.; Kumar, K. Kishore; Subrahmanyam, K.V.; Rao, S. Vijaya Bhaskara
Abstract: We analyzed 17 years (1993–2009) of horizontal winds measured by the medium frequency (MF) radar located at Tirunelveli (8.7°N, 77.8°E) and 10 years (2005–2014) of horizontal winds measured by a meteor radar located at Thumba (8.5°N, 77°E) to examine the seasonal, inter-annual, and solar cycle variability of the Quasi-Two Day Wave (QTDW) in the mesosphere and lower thermosphere region. These two radars are nearly co-located, but differ in their measurement technique. Comparison of the estimated QTDW amplitudes by the two radars shows that the amplitudes are larger in the meteor radar than those in the MF radar. The difference between the amplitudes is larger in May in the zonal component and in April and September in the meridional one. Furthermore, the differences are larger in the meridional component. The QTDWs in both the radars show a strong semi-annual oscillation (SAO). In addition, the meridional QTDW amplitudes of both the MF and meteor radars show a distinct enhancement in the month of October. While the whole spectra of QTDWs contribute to the SAO amplitudes, only 45–50 h waves contribute to the October enhancement. The amplitudes of the QTDWs, in general, show large inter-annual variability. The QTDW amplitudes from both the radars show modulation at period of quasi-biennial oscillation. The QTDWs of the MF radar show a small negative correlation with solar activity while those of meteor radar do not show any correlation. The above aspects are discussed in the light of current understanding of the QTDWs. Highlights: Long-term MF and meteor radar winds are used to study the quasi-two day waves (QTDWs). The QTDW amplitudes of the meteor radar are larger than those of the MF radar. The meridional QTDW amplitudes show an enhancement in October and a QBO. The QTDW amplitudes do not show any significant relation to solar cycle.